Pengaruh bahan baku sampah sayuran dan buah terhadap produksi biogas menggunakan starter Effective Mikroorganisme 4 - Dwi Irawan; Wahyudi Saipulloh; Ardyanto Darmanto (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2022)
Vegetable and fruit waste in traditional markets is very abundant, consisting of several waste materials left over from the sorting process for sale such as kale, cabbage, spinach, mustard greens, sweet potato leaves, cassava leaves and broccoli. Then fruit waste such as oranges, salak, melons, watermelons, and mangoes also adorn the market. In fact, the rest of the vegetables and fruits that are only used as waste can be used as materials to be processed to produce alternative energy, namely biogas. The purpose of the study was to determine the effect of vegetable and fruit waste raw materials with the addition of effective microorganisms (EM4) on the production and pressure of the biogas produced. The research was carried out with variations of raw materials for vegetable and fruit waste with a ratio of 50%; 50%, 60% ; 40%, and 60% ; 40%. The results in comparison 1 obtained a mass of 0.03169 kg with a pressure of 14751 N/m2, while in the second comparison, better results were obtained, the resulting pressure was 2552, 62 N/m2 and the mass obtained was 0.0323956 kg, then in the third comparison, the resulting pressure is 11635.66 N/m2 with a mass obtained of 0.315107 kg.